AB0569 Association between periodontal condition with disease duration and activity in colombian patients with spondyloarthritis. (23rd January 2014) - Londoño, J.; Romero-Sánchez, C.; Bautista-Molano, W.; Segura, S.; Cortes-Muñoz, A.; Castillo, D.; Muñoz, D.; Bello-Gualtero, J.; Lafaurie, G.; Valle-Oñate, R.
Abstract : Background: It has been suggested that rheumatic diseases may have additional underlying factors in common with chronic periodontitis. Spondyloarthritis (SpA) is associated with other inflammatory diseases such as psoriasis and uveitis; however, it is unclear whether these patients have a higher risk of inflammatory periodontal disease (PD). It is increasingly being realized that the systemic effects from PD makes substantial contributions to distal inflammatory processes. Few studies have addressed the possible link between ankylosing spondylitis (AS) and PD, and there is scarce data on whether SpA is associated with PD especially in our population. Objectives: To investigate the association between clinical indices of PD and disease activity characteristics in SpA patients receiving treatment. Methods: From a rheumatology outpatient clinic 30 SpA patients according to The European Spondylarthropathy Study Group (ESSG) classification criteria were enrolled over a seven month period. Patients with previous periodontal treatment, receiving TNF blockers, recent use of antibiotics, infections, edentulous, with malignancies or orthodontic treatment were excluded. Demographic, epidemiologic and disease specific variables were collected. Periodontal examination was performed by 2 experienced and calibrated periodontists, assessing bleeding on probing, plaque index, mean and extension of clinical attachment loss, mean pocket depth, inflammation and number of teeth. The extension of periodontitis was evaluated by pocket depth and clinical attachment and the severity of periodontitis was evaluated by clinical attachment loss. The association between clinical index of periodontitis and disease activity measures were was analyzed using chi square test. Results: Thirty patients were included in the study with mean age of 41.4 ± 10.7 years evolution time disease of 11.1± 8.0 years, mean BASDAI of 5.9±1.9 and mean BASFI of 5.0± 2.0 The diagnosis of AS was establish in 26, 7% (n=8), undifferentiated uSpA 63.3% (n=19) and reactive arthritis (ReA) 10% (n=3). HLA-B27 was present in 23.3% of the patients. The mean number of teeth was 26.6 IC 95% (25.5 - 27.7). Twenty three percent of the patients had sites with attachment loss ≥ 2mm, 50% had low plaque index, 43% lower levels of inflammation and 16.7% bleeding on probing. The percentage of sites with mean pocket depth was 2.36 and any patient had extension of periodontal inflammation. There was an association between the severity of periodontal involvement in patients with more than 5 years of evolution of the disease (p= 0.021), these patients had BASFI and BASDAI scores > 4.0, CRP <1.5 mg/L, HLA B27 negative, and number of teeth less than 20. Conclusions: These preliminary results shows that treated SpA patients with moderate grade of clinical activity present acceptable periodontal status, however, the time evolution of the SpA is a risk factor for the severity of the periodontal condition. This is the first study including different subtypes of SpA spectrum and not only AS. References: Keller J. Arthritis and Rheum 2013;65:167-173 Pischon N. Ann Rheum Dis 2010;69:34-38 Disclosure of Interest: None Declared